2022
DOI: 10.3389/fnut.2022.769626
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Aftermath of COVID-19 Outbreak in the Agro-Food System: An Exploratory Study of Experts' Perspectives

Abstract: The present study explored COVID-19 outbreak impacts on the food system in terms of agro-food production, distribution networks efficiency, and emerging food consumption patterns according to food experts' perspectives. Individual level data were selected from a sample of 59 executive managers of different domains representing agro-food businesses, agro-food cooperatives, and agro-food consulting firms and public institutions. The empirical analysis addressed the effects of the COVID-19 crisis to all the stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…In order to reveal the underlying components depicting students' attitudes toward plant-based diets and foods, an exploratory factor analysis (EFA) was applied, which comprises a widely used multivariate technique for investigation of scale validity and reduction of the dimensionality in a set of variables. The output of the EFA can be also adopted to facilitate further statistical analysis [Raptou et al [31]; Raptou & Manolas, [32,33,34]. In the present study, EFA was employed to test the potential interdependencies among the observed variables of the 18-item scale describing individuals' attitudes toward plant-based diets and food products, and uncover the underlying theoretical constructs referred as latent variables [35].…”
Section: Methods Of Analysismentioning
confidence: 99%
“…In order to reveal the underlying components depicting students' attitudes toward plant-based diets and foods, an exploratory factor analysis (EFA) was applied, which comprises a widely used multivariate technique for investigation of scale validity and reduction of the dimensionality in a set of variables. The output of the EFA can be also adopted to facilitate further statistical analysis [Raptou et al [31]; Raptou & Manolas, [32,33,34]. In the present study, EFA was employed to test the potential interdependencies among the observed variables of the 18-item scale describing individuals' attitudes toward plant-based diets and food products, and uncover the underlying theoretical constructs referred as latent variables [35].…”
Section: Methods Of Analysismentioning
confidence: 99%
“…The second relates to the COVID-19 pandemic that has also impacted the general population and, in particular, the agricultural workforce [24]. Since agriculture is the only provider of food inputs [25], the pandemic has undoubtedly created instability in the food sector along with global supply chain disruptions [26]. The last one is linked to the sustainability of the agricultural sector.…”
Section: Introductionmentioning
confidence: 99%
“…The health of workers involved in the food supply chain is important for safe food production to keep active the food supply chain until consumers. Many people are involved in the food supply chain, for example, raw materials suppliers, food processing workers, distributors, wholesalers, retail vendors, and different authorities where the lockdown and rapid spread of Covid-19 have tangled the entire supply chain from primary production to consumption ( Galanakis, 2020 , Charlebois and Music, 2021 ; Han et al, 2021 ; Raptou et al, 2022 ). Availability and access to safe food are most vulnerable during a pandemic due to multiple factors, different bodies, many people, and issues of public health that are directly connected with the entire food supply chain.…”
Section: Introductionmentioning
confidence: 99%